Perancangan Teknik Kriptografi Block Cipher Berbasis Pola Tarian Sajojo Papua - Dwayne Jeremy Euagellino Prihanto; Magdalena Ineke Pakereng (Ultima Computing : Jurnal Sistem Komputer, 2019)
Cryptography is a science to maintain the security and confidentiality of an information. In this research we designed Block Cipher Cryptography 64 bit Based on Tarian Sajojo Papua Pattern to build new cryptography. In this critique is designed with 10 rounds, where each round there are 4 processes. In each round there are 4 patterns for the plaintext process and 4 patterns for the key process. In second and fourth process is transformed with S-BOX table to get a more random ciphertext. Testing is also done using Avalanche Effect and Correlation value where the average character change reaches 49,69%, so it can be used as an alternative in securing data.